1996
DOI: 10.1046/j.1365-2567.1996.d01-760.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of small intestinal antigen‐presenting cells in the induction of T‐cell reactivity to soluble protein antigens: association between aberrant presentation in the lamina propria and oral tolerance

Abstract: The oral administration of soluble protein antigen results in profound immunological tolerance. However, the tissue location and function of antigen‐presenting cells (APC) that stimulate this response remain unclear. We have hypothesized that the properties of cells presenting antigen to naive T cells within the gut are involved, and therefore gut APC should stimulate T‐cell responses with different characteristics to those induced by other APC. To test this, we studied in vitro primary T‐cell responses follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…There are many APC such as DC in the mucosal LP, and we found that a substantial amount of orally administered protein antigen is taken up by APC in the LP, confirming previous findings of antigen loading at this site [17]. We now show directly that DC are likely to be responsible for this phenomenon and have characterized this population for the first time.…”
Section: Discussionsupporting
confidence: 89%
“…There are many APC such as DC in the mucosal LP, and we found that a substantial amount of orally administered protein antigen is taken up by APC in the LP, confirming previous findings of antigen loading at this site [17]. We now show directly that DC are likely to be responsible for this phenomenon and have characterized this population for the first time.…”
Section: Discussionsupporting
confidence: 89%
“…PP dendritic cells are distinct from those isolated from other secondary immune tissue and may contribute to the development of IL-10-secreting CD45RB low CD4 ϩ T cells. Dendritic cells residing in different tissues induce distinct immune responses from T cells (7,8,23). For instance, repetitive stimulation using immature human dendritic cells leads to differentiation of nonproliferative, IL-10-producing T cells with the ability to suppress proliferation of Th1 cells in vitro (16) Inhibiting IL-4, IL-10, and TGF-␤ in vitro did not appear to affect the functional response of PP T cells, suggesting that the effector function of these cells is established in vivo and is not readily modulated.…”
Section: Discussionmentioning
confidence: 99%
“…In the neighboring intrafollicular region of the PP, dendritic cells of a more mature phenotype than those found in the subepithelial dome lie in close association with T cells (6). Ag presentation by PP dendritic cells in vitro promotes splenic T cells to secrete IL-4, IL-6, and IL-10, in contrast to the proinflammatory cytokine, IFN-␥, induced by splenic dendritic cells (7)(8)(9). Furthermore, PP dendritic cells themselves secrete IL-10, an indication that, within the PP, T cells may be exposed to Ag in the presence of IL-10 (9).…”
mentioning
confidence: 99%
“…However, if Ag crosses into subepithelial spaces as free peptide, it is possible that binding to class II MHC molecules occurs on basal surfaces exposed to underlying LP. Studies from Harper et al (57) suggest that DC in the LP may present oral Ag to local T cells. These and other data support the notion that oral Ag permeates the epithelial barrier where it is presented to resident LP T cells by local APC (14).…”
Section: Discussionmentioning
confidence: 99%